Design an Interactive Material for Listening Sections for 11thGrades’ Students at Madrasah Aliyah - Abidin, Hasan (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2019)
Ignoring listening section during teaching-learning activity for Arabic language is a common in Madrasah Aliyah Negeri Jombang. And the causes are nevertheless of missing the fit materials as same as the used book, and lack teachers’ capability to produce the fit listening materials. The aims of this research areto produce interactive materials for listening section that is fit for the used book; and describe the effectiveness of using these interactive materials to improve students’ skill in listening and also to make a good atmosphere in teaching-learning activity.This is a research and development study and it was done in two steps,and the first step is producing The second step is applying the interactive materials in teaching-Learning activity. The researcher concluded that this interactive material is good and fit to use in a teaching-learning activity; this interactive material created a good condition and made the teaching-learning activity ran very well and also elicited students’ responses.